The Association Between Physical Activity and Cataracts Among 17, 777 People Aged 15–69 Years Residing in Spain. (3rd July 2020) - López-Sánchez, Guillermo F.; Pardhan, Shahina; Trott, Mike; Sánchez-Castillo, Sheila; Jackson, Sarah E; Tully, Mark; Gorely, Trish; López-Bueno, Rubén; Veronese, Nicola; Skalska, Maria; Jastrzębska, Joanna; Jastrzębski, Zbigniew; et al.
ABSTRACT: Purpose: The aim of the present study was to assess the association between levels of physical activity (PA) and the presence of cataracts in people aged 15–69 years residing in Spain. Methods: Cross-sectional data from the Spanish National Health Survey 2017 were analysed (n = 17, 777 ≥ 15 years; 52% females; self-weighting sample). The International Physical Activity Questionnaire (IPAQ) short form was used to measure PA. Total PA MET-minutes/week were calculated, and participants were divided into two categories: 1) Less than 600 MET-minutes/week. 2) At least 600 MET-minutes/week, equivalent to meeting current PA recommendations. Cataracts were self-reported in response to the question "Have you ever been diagnosed with cataracts?". Multivariable logistic regression was used to assess associations overall and by age groups (15–49, 50–64, and 65–69 years; 15–49 and 50–69 years). Covariates included in the analysis were sex, education, BMI (Body Mass Index), multimorbidity, smoking, and alcohol consumption. Results: The overall prevalence of cataract was 3.7%, and the overall prevalence of participating in less than 600 MET-minutes/week of PA was 30.2%. In the adjusted overall analysis, less than 600 MET-minutes/week of PA was associated with significantly higher odds for cataract: OR = 1.324 (95% CI = 1.116–1.571). Age-stratified analyses showed that the association between PA and cataract was significant only in the age groups of 65–69 years and 50–69 years. Conclusions: A significant association between PA and cataract was observed in people aged 15–69 years residing in Spain. Considering the impact on health and quality of life due to reduced PA in people with cataract, at least 600 MET-minutes/week activity should be promoted.